The Determinant Factors in Using E-Samsat Services on Motorized Vehicle Tax Payment in East Java, Indonesia - Rita Ambarwati; Mudji Astuti; Rohman Dijaya; Retna Fetty Idamayanti (Bina Nusantara University, 2021)
E-Samsat offers the service regarding motorized vehicle tax payment online. Still, in its implementation, it doesnot have many users. It is due to the community’s lack of awareness and the advantages that it can offer. Theresearch aimed to analyze the determinant factors in using the e-Samsat service in East Java. The effects of eachvariable (trust, awareness, ease of use, and intention to use) on each other were examined. The research wasconducted at Samsat joint office in Surabaya because it was the area with the largest motorized vehicle in EastJava. The research applied a quantitative approach. There were 200 respondents who were users of the service.They were selected using the cross-section technique through questionnaires. Then, data analysis used the PartialLeast Square Structural Equation Modeling (PLS-SEM) approach. Data analysis results indicate that almost allhypotheses are acceptable and have a significant effect on each other. However, trust does not have a significanteffect on the intention to use. The analysis of these factors can be recommended to increase the acceptance ofe-Samsat services in East Java. The research can help the government to make decisions related to e-government,create technological innovations that facilitate payments, and improve e-Samsat services quality.